Study of the properties of plant powders for the creation of phytocompositions of specialised and functional purpose - A. S. Kucher; S. S. Anufrik; O. V. Pavlova; V. G. Korniychuk; S. V. Vladimirov (Современная наука и инновации)
The article presents an analysis of the functional properties of plant raw materials (dogwood, pumpkin and apple). The analysis allowed us to conclude that it is promising to use phytocomponents to obtain food additives and create enriched and functional food products.  The objects of the study were powders from dogwood, pumpkin and apple. In the course of the studies, an assessment of the organoleptic and physicochemical properties of the powders was given. The expediency of adding powders to the composition of multicomponent food products to enrich them with minerals and improve sensory characteristics was shown.